PEMBERDAYAAN MASYARAKAT DALAM UPAYA PROGRAM KAMPUNG BERSIH DENGAN MEMANFAATKAN SAMPAH ORGANIK MENJADI PUPUK ORGANIK CAIR MEREK”PISWA” - Wartini yati; Joko Susanto; Rojali Rojali; Desembra Lisa; Prita Sari (Poltekkes Kemenkes Bandung, 2022)
ABSTRACT Until now,the waste problem has become an unresolved issue,especially organic waste. Independen and unproductive in reducing waste,not separating inorganic and organic waste into homework,accompanied by the absence of an integrated organic waste management house in the area. Clean village program is the goal for the handling of organic waste in the target areas in empowering enterpreunership development by utilizing organic waste into liquid organic fertilizer under the brand”Piswa”.The purpose of this empowerment is to practice the manufacture of liquid fertilizer by utilizing organic waste.The result showed that the total micronutrient Fe was 16.96 ppm,total Mn was 6.26 ppm,Zn was 1.61 ppm. Meanwhile,the micronutrient K2O reached 0.16 %,and Na+ was around 0.02 %.These result indicate that liquid organic fertilizer made has a selling value,if it is developed to the sales stage.The usefulness and skilla obtained can be furtner developed by making other types. So that the reduction of organic waste in the target area can be handled by utilizing organic waste into economic value.